Giant cell tumor occurring in familial Paget's disease of bone: Report of clinical characteristics and linkage analysis of a large pedigree1. (15th January 2013) - Gianfrancesco, Fernando; Rendina, Domenico; Merlotti, Daniela; Esposito, Teresa; Amyere, Mustapha; Formicola, Daniela; Muscariello, Riccardo; De Filippo, Gianpaolo; Strazzullo, Pasquale; Nuti, Ranuccio; Vikkula, Mikka; Gennari, Luigi
Abstract: Neoplastic degeneration represents a rare but serious complication of Paget's disease of bone (PDB). Although osteosarcomas have been described in up to 1% of PDB cases, giant cell tumors are less frequent and mainly occur in patients with polyostotic disease. We recently characterized a large pedigree with 14 affected members of whom four developed giant cell tumors at pagetic sites. The high number of affected subjects across multiple generations allowed us to better characterize the clinical phenotype and look for possible susceptibility loci. Of interest, all the affected members had polyostotic PDB, but subjects developing giant cell tumors showed an increased disease severity with a reduced clinical response to bisphosphonate treatment and an increased prevalence of bone pain, deformities, and fractures. Together with an increased occurrence of common pagetic complications, affected patients of this pedigree also evidenced a fivefold higher prevalence of coronary artery disease with respect to either the unaffected family members or a comparative cohort of 150 unrelated PDB cases from the same geographical area. This association was further enhanced in the four cases with PDB and giant cell tumors, all of them developing coronary artery disease before 60 years of age. Despite the early onset and the severe phenotype, PDB patients from this pedigree were negative for the presence of SQSTM1 or TNFRSF11A mutations, previously associated with enhanced disease severity. Genome‐wide linkage analysis identified six possible candidate regions on chromosomes 1, 5, 6, 8, 10, and 20. Because the chromosome 8 and 10 loci were next to the TNFRSF11B and OPTN genes, we extended the genetic screening to these two genes, but we failed to identify any causative mutation at both the genomic and transcription level, suggesting that a different genetic defect is associated with PDB and potentially giant cell tumor of bone in this pedigree. © 2013 American Society for Bone and Mineral Research.